PENGARUH CITRA MEREK DAN KEPERCAYAAN MEREK TERHADAP KEPUTUSAN PEMBELIAN PADA MARKETPLACE SHOPEE DI KOTA BANJARMASIN - Muhammad Arif Firdaus; Fitriyadi; Novia Nour Halisa; Setio Utomo (Smart Business Journal (SBJ), 2026)
Muhammad Arif Firdaus, 2110412310072, 2025. The Influence of Brand Image and Brand Trust on Purchase Decisions on the Shopee Marketplace in Banjarmasin, under the supervision of Fitriyadi. This study was conducted to identify and examine the partial and simultaneous effects of Brand Image and Brand Trust variables on purchase decisions on the Shopee marketplace in Banjarmasin. This research employed a quantitative approach, with the research location in Banjarmasin. A sample of 100 respondents who had previously purchased products on the Shopee marketplace was randomly selected using the accidental sampling technique. Data analysis was conducted using multiple linear regression with the assistance of IBM SPSS Statistics Version 26. The results of this study indicate that Brand Image has a significant partial effect on purchase decisions on the Shopee marketplace in Banjarmasin. Brand Trust also has a significant partial effect on purchase decisions on the Shopee marketplace in Banjarmasin. Furthermore, Brand Image and Brand Trust simultaneously have a significant effect on purchase decisions on the Shopee marketplace in Banjarmasin.